Gestão ágil e clientes cascata: desafios e alternativas para fábricas de software - Ana Carolina dos Santos Paes (2022)
Environments with changes and uncertainties demand a different management from the traditional, due to changes in projects involving innovation. The “agile” methods have spread quickly in recent years and are currently present in various areas of companies of all types and sizes. However, this diffusion associated with the assumptions of agile management regarding customer behavior can be very daring as it can raise a potential point of conflict in software development relationships aimed previously at traditional sectors. The area of study and practices of agile methods search to deepen the understanding in the customer needs to take them as objectively as possible to the product proposition seems to have neglected, especially for technological latecomers, the most primary needs of customers from traditional environments in their relationship with the software development approach. This work aimed to identify the problems that affect the agile management of projects that involve customers associated with contexts considered more traditional to understand how it is possible to mitigate these obstacles, seeking a project approach with greater chances of success. Consequently, the research was developed using data collection and analysis techniques typical of case studies and semi-structured interviews that contributed to assist in the development of the work. A preliminary research was done, afterwards, 7 interviews with managers and 2 with customers who use the agile management methods in software projects that are applied in environments focused on traditional one. Thereby, it was observed that there are some challenges of integrating “waterfall customers” in agile management projects, as well as alternatives for contouring and adapting to agile management. In addition, some reasons for failures in agile projects were found and factors/actions related to the type of management seeking the success of the project. Keywords: agile management, project management